JUAL BELI MUKHADHARAH PERSPEKTIF HADIS: ANALISIS KRITIK SANAD DAN MATAN - Nasrin Nazar; Tasbih Tasbih (AL-BAYAN INSTITUTE, 2025)
This study aims to examine the prohibition of mukhadharah (sale of unripe agricultural products) from the perspective of Hadith. Mukhadharah refers to transactions involving fruits or crops that are not yet ripe and whose quality is uncertain. In Islamic law, this practice is prohibited due to the presence of gharar (uncertainty), which may harm one of the parties. This qualitative research employs hadith takhrij and critical analysis methods. The data are derived from major hadith collections such as Sahih Muslim, Sunan Abu Dawud, Sunan al-Nasa’i, and others. The findings reveal that the hadiths prohibiting mukhadharah are classified as sahih in terms of both sanad (chain of narrators) and matn (text). Matn analysis indicates no contradiction with the Qur’an, other authentic hadiths, historical facts, or rational reasoning. Therefore, the prohibition reflects the Islamic emphasis on justice and clarity in commercial transactions.